Accelerators : High accuracy amplitude and phase measurements based on a double heterodyne architecture. (14th January 2015) - Zhao, Dan-Yang; Wang, Guang-Wei; Pan, Wei-Min; Sun, Yi; Qiu, Feng; Zhang, Juan; Mi, Zheng-Hui; Lin, Hai-Ying; Sha, Peng; Wang, Qun-Yao; Xu, Bo; Ma, Qiang
Abstract: In the digital low level RF (LLRF) system of a circular (particle) accelerator, the RF field signal is usually down converted to a fixed intermediate frequency (IF). The ratio of IF and sampling frequency determines the processing required, and differs in various LLRF systems. It is generally desirable to design a universally compatible architecture for different IFs with no change to the sampling frequency and algorithm. A new RF detection method based on a double heterodyne architecture for wide IF range has been developed, which achieves the high accuracy requirement of modern LLRF. In this paper, the relation of IF and phase error is systematically analyzed for the first time and verified by experiments. The effects of temperature drift for 16 h IF detection are inhibited by the amplitude and phase calibrations.